Rancang Bangun Sistem Monitoring dan Pembatasan Zona Operasional Kendaraan Bermotor Roda Dua berbasis Website dan Arduino - Arief Nugraha; Mochamad Subianto; Windra Swastika (Maranatha University Press, 2019)
Two-wheeled motorized vehicles provide a separate role in shortening travel time and can also save travel costs compared to using public transportation (city transportation). With the availability of motorized vehicle facilities for students, parents do not have to bother with their child's business going to school, so children can go to their own school. However, the presence of motorized vehicles brought by students to school resulted in a decrease in parental supervision of their children. Therefore, this study aims to create a monitoring and control system for website-based motor vehicle operations with the help of Arduino Uno, Neo Ublox 6M GPS Module, and SIM900 GSM Shield which is installed into a motorized vehicle that is useful as a motor vehicle controller. Using this system can increase parental supervision of children when using motorized vehicles. Arduino installed in motorized vehicles then waits for the GPS signal from the Neo Ublox 6M GPS Module, after that the GPS data will be sent to the web service using the SIM900 GSM Shield. The web service will calculate the distance between 2 points, that is, the zone of the zone with the location of the prototype after comparison with the size of the zone that has been determined, if the calculation results exceed the zone, the prototype will turn off the engine. From the results of GPS accuracy testing using HDOP has produced a good rating and the use of the GPS NEO module is feasible to be used as the current location data provider and also the prototype response to the zone has been tested and produces an average value of 14.8 seconds. Keywords: GPS, Arduino Uno, GPS Neo Ublox 6M module, GSM Shield SIM900, Vehicles monitoring system, web service.